2000
DOI: 10.1037/0893-164x.14.2.197
|View full text |Cite
|
Sign up to set email alerts
|

Predicting substance abuse among youth with, or at high risk for, HIV.

Abstract: This article describes data from 4,111 males and 4,085 females participating in 10 HIV/AIDS service demonstration projects. The sample was diverse in age, gender, ethnicity, HIV status, and risk for HIV transmission. Logistic regression was used to determine the attributes that best predict substance abuse. Males who were younger; HIV positive; homeless; involved in the criminal justice system; had a sexually transmitted disease (STD); engaged in survival sex; and participated in risky sex with men, women, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 26 publications
1
17
0
2
Order By: Relevance
“…In one study, for example, it was demonstrated that the odds of experiencing a violent act, including being beaten, witnessing a shooting or stabbing or thinking of hurting someone else, are 2 to 3 higher for street-based youth than other youth (Irwin et al, 1996). Furthermore, the probability that street-youth will experience violence likely increases in accordance with the amount of time spent on the street (Huba and Melchior, 2000;Fuller et al, 2001), further demonstrating the incredible need for interventions that prevent at-risk youth from either becoming or remaining homeless.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In one study, for example, it was demonstrated that the odds of experiencing a violent act, including being beaten, witnessing a shooting or stabbing or thinking of hurting someone else, are 2 to 3 higher for street-based youth than other youth (Irwin et al, 1996). Furthermore, the probability that street-youth will experience violence likely increases in accordance with the amount of time spent on the street (Huba and Melchior, 2000;Fuller et al, 2001), further demonstrating the incredible need for interventions that prevent at-risk youth from either becoming or remaining homeless.…”
Section: Discussionmentioning
confidence: 86%
“…Given the public spaces which homeless youth often spend most of their lives, particularly in urban settings such as downtown Vancouver, this finding is not surprising. Homeless youth, including those in our study, are at-risk for and likely to be subjected to violence, whether they are themselves victimized or are a witness to a violent event (Huba and Melchior, 2000). In one study, for example, it was demonstrated that the odds of experiencing a violent act, including being beaten, witnessing a shooting or stabbing or thinking of hurting someone else, are 2 to 3 higher for street-based youth than other youth (Irwin et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Use of alcohol and other drugs increases risk of HIV infection (Amaro et al, 2001;Caetano & Hines, 1995;DeHovitz et al, 1994), partly through association with high-risk sexual behavior such as having multiple sex partners and partners who are themselves at risk for HIV/AIDS (Avins et al, 1994;Malow, Devieux, Jennings, Lucenko, & Kalichman, 2001;Clements, Gleghorn, Garcia, Katz, & Marx, 1997;Edlin et al, 1994;Huba et al, 2000;Martinez et al, 1998;Schilling et al, 1994;Semple, Zians, Grant, & Patterson, 2005;Windle, 1997).…”
Section: Introductionmentioning
confidence: 97%
“…In one study on urban gay men, for example, multiple and frequent drug use was more likely to be reported by HIV-positive men [3] . HIV infection is also positively correlated with increased drug use among high risk youths [4] . Among injection drug users recruited for substance abuse treatment, HIV infected persons ceased injecting drugs sooner than non-infected users, but were also quicker to subsequent relapse [5] .…”
Section: Introductionmentioning
confidence: 99%